Kaaitheater 85. (Brussel : Kaaitheater, 1985)
Gallotta, Jean-Claude ; Groupe Emile Dubois ; Vidal, Albert ; Vanrunxt, Marc ; Rijnders, Gerardjan ; Zuiderlijk Toneel Globe ; Clark, Michael and Company ; Van Hemelrijck, Pat ; George Coates Perfromance Works ; Rosas ; Fabre, Jan ; Paxton, Steve ; Van Haegenborgh, Luc
Nederlands & Frans & Engels
boek